2022
DOI: 10.1063/5.0114688
|View full text |Cite
|
Sign up to set email alerts
|

Dual exponential coupled cluster theory: Unitary adaptation, implementation in the variational quantum eigensolver framework and pilot applications

Abstract: In this paper, we have developed a unitary variant of a double exponential coupled cluster theory, which is capable of handling molecular strong correlation with arbitrary electronic complexity. With the Hartree-Fock determinant taken as the reference, we introduce a sequential product of parametrized unitary ansatze. While the first unitary, containing the excitation operators, acts directly on the reference determinant, the second unitary, containing a set of rank-two, vacuum-annihilating scattering operator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…While the state preparation through VQE has assumed an ideal quantum environment, one may also take into account the effect of finite number of measurements during the state preparation. Furthermore, it would be interesting to study the success probability of prepared state with more robust and low depth unitary ansätze (like k‐UpCCGSD [28], UiCCSDn [51]). These will be highlighted in one of our future publications.…”
Section: Discussionmentioning
confidence: 99%
“…While the state preparation through VQE has assumed an ideal quantum environment, one may also take into account the effect of finite number of measurements during the state preparation. Furthermore, it would be interesting to study the success probability of prepared state with more robust and low depth unitary ansätze (like k‐UpCCGSD [28], UiCCSDn [51]). These will be highlighted in one of our future publications.…”
Section: Discussionmentioning
confidence: 99%
“…The interwoven structure of the ansatz that includes high rank correlation through its decomposition into lower rank operators is reminiscent of a double exponential (factorized) coupled cluster ansatz 41 and its unitarized variant. 7 Such double exponential structure of the waveoperator in terms of two-body operators is crucial for the exactness of the wavefunction for which the variational minimum analytically satises the contracted Schrödinger equation (CSE) 42 a necessary and sufficient condition for the wavefunction to satisfy the Schrödinger equation. Contrarily, the wavefunctions generated from a single exponential with generalized two-body operators 43,44 do not satisfy the CSE.…”
Section: 35mentioning
confidence: 99%
“…For this comparison, we do not use additional error mitigation techniques. 35,[58][59][60][61][62][63] 4 Conclusions and future outlook…”
Section: Implementation Of Rbm-ducc Under Noisementioning
confidence: 99%
“…Recent works have proposed novel ways to improve the efficiency of the VQE algorithm, such as (i) proposing newer chemically inspired ansatzes like k-UpCCGSD with lower circuit depths than that of the UCCSD ansatz, (ii) modifying the existing UCCSD ansatz through operator screening or by using the newer variants of UCCSD like dual exponential variant for reducing the circuit depth, and (iii) by employing embedding schemes and entanglement forging techniques for reducing the qubit requirement while working with larger molecules. , Specific to the issue with the parameter optimization in VQE, Tao et al proposed the deep neural network (DNN)-VQE method, where a DNN model is used to predict the final optimized variational parameters for the quantum circuit . Using such parameters as the initial point for a VQE calculation, the authors showed that the DNN-VQE method is able to accurately construct the PESs of several small molecules such as H 2 , LiH, BeH 2 , and H 4 .…”
Section: Introductionmentioning
confidence: 99%